A systematic evaluation of cutaneous microcirculation in the foot using post‐occlusive reactive hyperemia. (5th May 2021) - Balasubramanian, Gayathri; Chockalingam, Nachiappan; Naemi, Roozbeh
Abstract: Objectives: Cutaneous microcirculatory impairments are associated with skin injury to the foot. Post‐Occlusive reactive hyperemia (PORH) is one of the quick and easy methods to assess microcirculatory function. However, there are variations in the protocols currently used. Hence, this study aimed to systematically investigate the reproducibility of PORH protocols with minimal occlusion time in the foot. Methods: Post‐Occlusive reactive hyperemia was measured using 12 different protocols (three occlusion times, two occlusion sites and with or without temperature control) in 25 healthy adults. Each of the 12 different protocols was repeated three times, and the intraclass correlation coefficient (ICC) was calculated. Results: Intraclass correlation coefficient showed that that ankle level occlusion produced moderate to excellent reproducibility for most PORH measures. In the right foot, 30‐ and 60‐s ankle level occlusion without temperature control showed ICC of >0.40 for all parameters except the area of hyperemia (ICC = −0.36) and biological zero to peak flow percent change (ICC = −0.46). In the left foot, 30‐s ankle level occlusion without temperature control showed ICC of >0.40 for all parameters except time to latency (ICC = 0.29), after hyperemia (ICC = 0.37), and max (ICC = −0.01), and area of hyperemia (ICC = −0.36). But the 60‐s protocol showed ICC > 0.40 for all except time to max (ICC = 0.38). In the hallux protocols, all three 10‐, 30‐, and 60‐s protocols without temperature control showed moderate to excellent reproducibility (ICC > 0.40). In most cases, the temporal and area under the perfusion‐time curve parameters showed poor reproducibility. Conclusion: Post‐Occlusive reactive hyperemia can be tested efficiently with a minimal occlusion time of 10 s with hallux occlusion and 30 s with ankle occlusion in the foot. This can suggest that microcirculatory assessment is feasible in routine practice and can potentially be included for routine assessment of foot in people with diabetes.